The Concept of Tasyabbuh in Hadith: A Comparative Study of Classical and Modern Interpretations - Yahya, Muhammad Ar Rafi (West Science Islamic Studies, 2026)
One of the hadiths that has broad implications for the formation of Muslim identity is the hadith prohibiting resemblance to non-Muslims (tasyabbuh). In contemporary social realities, this hadith is frequently invoked as a basis for legal debates concerning various social practices, cultural expressions, and symbols that intersect with non-Muslim traditions. This study aims to examine the meaning of the hadith prohibiting tasyabbuh through a comparative analysis of the perspectives of classical and contemporary scholars. This research employs a library-based qualitative method with a comparative approach, grounded in textual analysis of the hadith and scholarly interpretations across different periods. The findings indicate that both classical and contemporary scholars share fundamental principles in understanding the hadith on tasyabbuh, particularly in affirming the prohibition of resembling non-Muslims in matters of creed (ʿaqīdah), worship (ʿibādah), and religious symbols (shiʿār al-dīn). The differences that emerge are primarily methodological, especially in responding to modern social and cultural changes. Contemporary scholars emphasize the classification of forms of tasyabbuh, the distinction between acts of worship and customary practices, as well as considerations of intention and potential harm (mafsadah). Thus, these differences are not contradictory but complementary, aiming to safeguard the purity of faith and the identity of the Muslim community in accordance with the context of each era.